An unusual case of parapharyngeal desmoid fibromatosis - A rare case report - Chinmayee P Joshi; Nandini Jitendra Gupta (Wolters Kluwer Medknow Publications, 2022)
Desmoid fibromatosis (DF) is a rare locally aggressive, connective tissue malignancy developing in musculoaponeurotic tissues with an incidence of 2-4 per million population. We presented a case of a 3-year-old patient with a left parapharyngeal mass, histopathological examination suggesting DF, who underwent complete surgical excision without recurrence or requirement of cardiac resynchronization therapy.